Late Prenatal Diagnosis of Hydrometrocolpos Secondary to a Cloacal Anomaly by Abdominal Ultrasonography with Complementary Magnetic Resonance Imaging - Yun-Hsiang Hung; Ching-Chang Tsai; Chia-Yu Ou; Bi-Hua Cheng; Pao-Chu Yu; Te-Yao Hsu (Elsevier, 2008)
Summary: Objective: Prenatal diagnosis of a cloacal anomaly is difficult. Magnetic resonance imaging (MRI) can assist in the identification of the connection and continuity of a cystic mass to confirm the diagnosis of a cloacal anomaly. Case Reports: In the first case, a fetal abdominal cystic mass was observed at 32 weeks of gestation. Ultrasonography revealed a retrovesical septate hypoechoic mass with bilateral hydronephrosis. MRI demonstrated a midline cystic mass connected to a dilated uterus and a possible fistula between the bladder and vagina. In the second case, a fetal abdominal septate cystic mass was identified using ultrasonography at 34 weeks of gestation. MRI was performed and demonstrated hydrocolpos/hydrometrocolpos originating from a uterine didelphis with left dysgenesis and a possible vesicovaginal fistula. After birth, both newborns underwent immediate surgical intervention with good outcomes. Conclusion: MRI facilitated the prenatal diagnosis of cloacal anomalies and allowed additional time for parental counseling and planning of the delivery method with subsequent neonatal intensive care and surgical and urologic consultations. Key Words: cloacal anomaly, hydrometrocolpos, magnetic resonance imaging